Social networks relevance as a promotion tool in the hotel industry: the case of Porto hotels - Cunha, Manuela (2021)
Social Networks are becoming essential for interaction, dialogue and connectivity with customers. Tourism in general, and hospitality, due to its intrinsic characteristics, has been known to be particularly affected by this trend. The existing platforms, make the tourists also a promoter / detractor of tourist destinations and attractions through the sharing of publications, pictures or experiences. In this sense, the objective of the present investigation is to understand the influence that generic and non- generic social networks have on the hotel sector, both from the perspective of the hotel and the consumer. To this end, data were collected on several digital channels from twelve hotels located in the Portuguese city of Porto. According the results obtained, it was clear that the content and presence vary according to the stars of the hotels and the type of the social network analyzed.